Antimicrobial activity of an Algerian medicinal plant: Carthamus caeruleus L. - Karima, Saffidine; Farida, Sahli; Mohamed Mihoub, Zerroug (Pharmacognosy Communications)
Background: Medicinal plants constitute a source of bioactive substances to treat chronic as well as infectious diseases in many countries of the world. A wide range of natural antimicrobial agents can either inhibit the growth of microorganisms or kill them and represent a good alternative to chemical drugs for treatment of various infectious diseases to face the phenomena of germ resistance. Methods: In our study, we have used plants of the genus Carthamus, which are widely distributed in the Mediterranean region and have been traditionally used to treat skin diseases and burns. Our experiments were carried on the roots and leaves of a Carthamus species growing in Sétif area in the North-East of Algeria, in order to evaluate its antimicrobial activity. Results: Our results showed potent activity of root and leaf extracts in vitro against Gram-negative and Gram-positive bacteria strains as well as against pathogenic fungus. Variable antimicrobial effects of different extracts have been obtained against the tested microorganisms. For root extracts, high inhibition zone of 25 mm was exhibited on Candida albicans, 20 mm against Staphylococcus aureus and Bacillus cereus, and 15 mm on Acinetobacter bowie. Moderate activity of 12 mm and 11 mm was obtained for pathogenic plant fungi (Aschochyta rabiei and Fusarium Var coerileum) and lowest activity of 8.3 mm was obtained for Fusarium oxysporum albidinis. Leaf extracts were only effective against Acinetobacter bowii and Staphylococcus aureus with inhibition zones of 18 and 20 mm respectively. The root extracts were more active than the leave extracts against the tested microorganisms.